Archaeological Stratigraphy, Flat Ontology and Thin Description. A Note on (Inter)disciplinary Dialogue - Staša Babić (University of Belgrade, 2019)
Over the last decades, some archaeologists have adopted the approaches from philosophy and anthropology that may loosely be denoted by the term new materialism. The key assumptions are that archaeological investigation, regardless of the theoretical stance applied, has always been burdened by the modern mode of thinking and dichotomies such as nature/culture or subject/object, wherefrom stems the anthropocentric approach to the study of objects, primarily in respect to humans. It is suggested that the reality consists of a plethora of diverse elements, all deserving equal attention and all their existences being of equal relevance. Objects, animals, plants, all have the potential to act in a network of equal actors. A researcher must therefore respect the flat ontology, where none of the actors has primacy.